How to Design Subnational Fiscal Rules : A Primer - Eyraud, Luc (IMF How To Notes; How-To Note ;, 2020)
This note discusses how to design subnational fiscal rules, including how to select them and calibrate them. It expands on the guidance provided at the national level on rule selection and calibration in IMF (2018a) and IMF (2018b). Thinking on subnational fiscal rules is still evolving, including their effectiveness (for example, Heinemann, Moessinger, and Yeter 2018; Kotia and Lledo 2016; Foremny 2014), and this note only provides a first analysis based on international experiences and the technical assistance provided by the IMF. Main findings are summarized in Box 1. The note is divided into five sections. The first section defines fiscal rules. The second section discusses the rationale for subnational rules. The third section provides some guidance on how to select the appropriate rule(s) and whether they should differ across individual jurisdictions. The fourth section explores the issue of flexibility by looking at how rules should adjust to shocks. Finally, the last section focuses on the 'calibration' of the rules.